A Comparative Study on Equity, Commodity, Currency Derivatives in India - Evidence from Future Market with special reference to BSE Ltd, Mumbai - Sathya,, S. (International Journal of Scientific Research and Management (IJSRM), 2015)
The study compares the equity, commodity, and currency derivatives in India – evidence from future market. This study focus on the risk and return associated with derivatives used in equity, commodity, and currency market in India. The average and standard deviation to access the risk and return factor and also comparative tool for correlation analysis were used to find out relationship among risk and return. It is found that the risk premium of equity is essentially the same as commodity, equity returns are negatively correlated with commodity return and currency return and also found that the equity, commodity, and currency of derivatives are used for hedging purpose